Effect of Arbuscular Mycorrhizal Fungi, Selenium and Biochar on Photosynthetic Pigments and Antioxidant Enzyme Activity Under Arsenic Stress in Mung Bean (Vigna radiata) - Alam, Mohammad Zahangeer; McGee, Rebecca; Hoque, Md. Anamul; Ahammed, Golam Jalal; Carpenter-Boggs, Lynne (Frontiers in Physiology, 2019)
Environmental perturbations alter biochemical compounds in food crops. Arsenic (As), a toxic metalloid, is known to affect the cultivation of food crops in many regions of the world; however, the changes in chlorophyll, catalase and proline in response to As stress and the role of stress relief substances remain largely unknown in mung bean (Vigna radiate L.). In this study, bio chars (BC), arbuscular mycorrhizal fungi (AMF) and selenium (Se) were applied to the soils as stress relief substances under 30 mg kg-1 As stress and the effects of BC, AMF and Se on chlorophyll a, chlorophyll b, total chlorophyll, catalase activity and proline content were studied in different mung bean genotypes. Under As stress, the chlorophyll a, chlorophyll b and total chlorophyll contents in BARI mung 3, BARI mung 5 and BARI mung 8 were found statistically similar. Meanwhile, catalase activity increased in comparison to the control due to the application of bio char, AMF and Se in mung bean crops. However, proline was found significantly lower in AMF, BC and Se-treated mung bean. This indicates that oxidative stress was potentially minimized in As-stressed mung bean crops due to the application of these stress relief substances. Notably, AMF substance was relatively effective against As stress in comparison to BC, and Se. It is concluded that BC, AMF and Se are all highly effective in enhancing the antioxidant defense as well as nutritional quality of mung bean crops under As stress.